2006
DOI: 10.2139/ssrn.789725
|View full text |Cite
|
Sign up to set email alerts
|

Does Asymmetric Information Drive Capital Structure Decisions?

Abstract: Using a novel information asymmetry index based on measures of adverse selection developed by the market microstructure literature, we test whether information asymmetry is an important determinant of capital structure decisions, as suggested by the pecking order theory. Our index relies exclusively on measures of the market's assessment of adverse selection risk rather than on ex ante firm characteristics. We find that information asymmetry does affect the capital structure decisions of U.S. firms over the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(207 citation statements)
references
References 108 publications
9
189
0
9
Order By: Relevance
“…This outcome is reinforced by the finding of Cheung et al (2015) who further suggest that stock market liquidity is relevant for firm value through corporate governance. A number of papers focus on examining the relationship between stock market liquidity and the capital structure decision of firms (Morellec 2001;Lesmond et al 2008;Bharath et al 2009;Lipson & Mortal 2009;Sibilkov 2009). These papers argue that firm managers tend to be influenced by stock market signal in their corporate finance decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This outcome is reinforced by the finding of Cheung et al (2015) who further suggest that stock market liquidity is relevant for firm value through corporate governance. A number of papers focus on examining the relationship between stock market liquidity and the capital structure decision of firms (Morellec 2001;Lesmond et al 2008;Bharath et al 2009;Lipson & Mortal 2009;Sibilkov 2009). These papers argue that firm managers tend to be influenced by stock market signal in their corporate finance decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies found that increased information asymmetry are associated with reduced liquidity of a company's stocks (Agarwal & O'Hara, 2007;Bharath, Pasquariello & Wu, 2009), suggesting that share liquidity and information asymmetry can be negatively correlated.…”
Section: Control Variablesmentioning
confidence: 98%
“…From exploring the financing theories in the literature; tangibility, growth, firm size and profitability have influences on pecking order theory (Bharath et al, 2009;Frank and Goyal, 2003;Leary and Roberts, 2010). Frank and Goyal (2009) indicate that firms that have more tangible assets tend to have higher leverage.…”
Section: Capital Structurementioning
confidence: 99%